The nutritional and bioactive properties of probiotic-enriched barley-buttermilk beverages - Algheshairy, Reham M.; Ali, Asmahan A.; Alharbi, Hend F.; Bushnaq, Taqwa; Alsaleem, Khalid A.; Alsanei, Woroud A.; Mohamed Ahmed, Isam A.; Barakat, Hassan; Sakr, Sally S. (Frontiers in Sustainable Food Systems, 2025)
ObjectivesFermented cereal beverages are vital for the nutrition of resource-poor populations, as they offer affordable, energy-rich, and safe beverage options. These beverages are integral to traditional food cultures, particularly in Africa and Asia, and they help support local economies through small-scale production and consumption. Probiotic beverages received great attention in last decades due to their positive impacts on the prevention of diseases and promotion of human health. The improvement of traditionally cereal-based fermented beverages is one of the main approaches for production and commercialization of probiotic beverages. Barely-based Sobia beverage (BBSB), is one of the most popular fermented cereal-based probiotic beverages with rising demand in various countries, however, its traditional production method is time-consuming and eliminates scaling up production. Therefore, this study aimed at investigating the impacts of processing methods [traditional (TM) and improved (IM)] on the physicochemical, microbiological and nutritional quality of traditional and improved concentrated BBSB.MethodsModification of the TM was done by pasteurization process and incorporation of butter milk, date powder, and ABT-5 probiotic starter culture (Lactobacillus acidophilus LA-5, Bifidobacterium spp. BB-12, and Streptococcus thermophilus) in the formulas. Concentrated BBSB in water or buttermilk (9% total solids) were examined for microbiological quality, total phenolic content (TPC), antioxidant activity (AOA), γ-aminobutyric acid (GABA) content, β-glucan content, volatiles by HS-GC–MS, and in vitro hydrolysis (HI) and glycemic (GI) indices.ResultsResults indicated that concentrated BBSB in buttermilk following the IM showed high levels of lactic acid bacteria (LAB), TPC content, DPPH and ABTS radical scavenging activities, improved microbial quality, high GABA content, and absence of coliform bacteria compared to concentrated BBSB following TM. The highest range of β-glucan was remarked in concentrated BBSB in buttermilk fermented by combining ABT-5 with backer’s yeast regardless of sugar source. The HS-GC–MS analysis identified and quantified 28 volatile compounds. The predominant volatiles in concentrated BBSB were terpenes (49.67–77.56%) followed by alcohols (8.08–32.65%). The HI and GI values were increased for concentrated BBSB in buttermilk (IM) compared to that in water (TM). Application of ABT-5 and bakers’ yeast mixture in the presence of date powder increased HI and GI values of concentrated BBSB.ConclusionIn conclusion, using the IM enhanced the microbiological and nutritional qualities, increased the health-promoting compounds, improved the in vitro Glycemic index and could be recommended for scaling up commercial applications to produce concentrated BBSB.